THE INFLUENCE OF LECTURER’S PEDAGOGIC AND PROFESSIONAL COMPETENCES TOWARD STUDENTS’ WRITING PROFICIENCY AT POLITEKNIK ILMU PELAYARAN MAKASSAR - Sunarlia Limbong (JURNAL VENUS, 2018)
Foreign language teaching and learning, especially English language for communication as sea is a part of curriculum in all maritime colleges. This is because English has been used as the sea language in a whole world. As a foreign language in Indonesia, it requires more skills to be able to teach it because besides teaching the subject matters, the lecturer’s competence is necessary for the successful learning process. The research aimed at finding out: (1) the profile of students’ writing skill at deck department of Politeknik Ilmu Pelayaran Makassar, (2) the influence of pedagogic competence toward students’ writing proficiency at Deck Department of Politeknik Ilmu Pelayaran Makassar, (3) the influence of professional competence toward students’ writing proficiency at Deck Department of Politeknik Ilmu Pelayaran Makassar. The research applied quantitative design with applying the ex post facto method. The subject of this research consists of second semester of Deck (Nautical) department of Politeknik Ilmu Pelayaran Makassar. The data was collected using the result of student’s writing proficiency and questionnaire. The quantitative data was first tabulated and then classified according to the given score ranges, and finally categorized in regard to the given criteria. The result of data analysis showed that (1) The profile of students’ writing skill is categorized into moderate category (2) Pedagogic competence has positive and significant influence towards students' writing proficiency. The correlation between the pedagogic competence and the students' writing proficiency is 0.783 or 78.3%. (3) Professional competence has positive and significant influence towards students' writing proficiency. The correlation between the professional competence and the students' writing proficiency is 0.529 or 52.9%.